Predicting the global combustion behaviors of petroleum-derived and alternative jet fuels by simple fuel property measurements. (15th March 2016) - Won, Sang Hee; Veloo, Peter S.; Dooley, Stephen; Santner, Jeffrey; Haas, Francis M.; Ju, Yiguang; Dryer, Frederick L.
Abstract: Pre-vaporized global combustion behaviors of a petroleum-derived jet fuel (JP-8), five alternative jet fuels (Shell SPK, Sasol IPK, HRJ Camelina, HRJ Tallow, and Gevo ATJ), and five 50/50 (liquid volume) blends of JP-8/alternative fuels are experimentally examined and compared. Three experiments are performed to investigate the gas-phase combustion behaviors of the tested fuel samples: (1) global oxidative species profiles in a variable pressure flow reactor, (2) diffusion flame extinction in a counterflow burner, and (3) premixed flame initiation in a heated spherical combustion chamber. Multivariate linear regression methods have been applied to investigate the sensitivities of pre-vaporized global combustion behaviors to individual combustion property targets of the fuels, including Derived Cetane Number (DCN), H/C ratio, mean molecular weight, and smoke point. As a proof of concept for fuel screening tool based on the standardized fuel property measurements, a "combustion property target (CPT) index" based upon this regression analysis is found to show promise as a rapid means to evaluate the global pre-vaporized combustion behaviors of the tested fuel samples against each other as well as the spectrum of JP-8 fuels found in use. The present work suggests the applicability of such a methodology not only as an expeditious fuel screening tool for assessing the fully pre-vaporized, kinetically coupled behaviors of emerging alternative jet fuel candidates, but further supports the use of combustion property targets in developing kinetic models that are specific to each real fuel.